Peak BMD Assessment in a Chinese Infantry Recruit Group - Yang, J.; Sun, J.; Luo, F.; Sun, Q.; Zhao, L.; Su, N.; Du, X.; Huang, H.; Shen, Y.; Chen, L. (International Journal of Sports Medicine, 2011)
Peak bone mass is an important factor influencing the occurrence of osteoporosis and osteoporotic fracture in adulthood. We measured the areal bone mineral density (BMD) in a Chinese male infantry recruit group ranging in age from 17 to 23 years and subsequently assessed peak BMD at the lumbar vertebrae and hip. This study included 812 Chinese men of Han ethnicity from 11 provinces and municipalities of China. The BMD, bone mineral content and the bone area of the lumbar vertebrae (L1-4), left femoral neck and total hip were measured using dual-energy X-ray absorptiometry. Height, weight, waist and hip circumference were also measured at the same time. BMD at the lumbar vertebrae, femoral neck and total hip reached a plateau at 22 years of age. The peak value of BMD at these 3 sites was 1.209±0.175, 1.098±0.177 and 1.122±0.151 (g/cm2), respectively. Stepwise regression analysis showed that age and weight most contributed to the variance in BMD (P<0.001). The average age when reaching peak BMD in this study is earlier than the ages reported in previous studies, and the value of peak BMD is higher than that reported previously in Chinese males. This study provides the newest peak BMD data on Chinese men.
Keywords: peak bone mineral density; Chinese; male; Han ethnicity